View of school - Dodds, St Philip, Barbados - (:unkn) unknown (My University, 2012)
A view of the buildings at the reformatory school Dodds in St Philip, Barbados, in the 1920s. A few boys stand at attention while being watched by an adult. The present day Dodds Industrial School for Boys is a residential school for children who have been referred by Juvenile Courts for detention. Handwritten note at back of card reads: "Arrived on the 3rd June, signed E. Bradshaw." Addressed to "Miss Heywood, [leigh], Glastonbury, Somerset, England." from "Bruce [Y]ale, St. Andrew, Barbados, W.I."
Landscape; black and white
Keywords: Reformatories; Boys; Buildings; Postcards; Men; Government Industrial School